2020
DOI: 10.1055/s-0040-1710589
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Vena Cava Filter Use in Patients with Cancer-Associated Venous Thromboembolism and Contraindications to Anticoagulation

Abstract: Abstract Background The association between the use of inferior vena cava filters (IVCFs) and outcomes among patients with cancer-associated thromboembolism (CT) and contraindications to anticoagulation remains unclear. Methods In this prospective cohort study of patients with CT from the Registro Informatizado de la Enfermedad TromboEmbólica Registry, we assessed the association between IVCF insertion due to contraindication to anticoagulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A population-based study of cancer patients with acute lower extremity DVT demonstrated an improvement in PE-free survival on long-term follow-up in patients with IVCF insertion (for any indication) compared to those without (HR, 0.69; 95% CI, 0.64-0.75). 106 The proportion of new DVT among patients who received IVCF was slightly lower than in patients who did not receive IVCF (18.7% versus 22.1%; respectively, P < 0.001). A prospective cohort study of cancer patients with acute PE or lower extremity DVT used propensity score matching to compare 30-day outcomes between patients with IVCF placement because of a significant bleeding risk versus patients without IVCF placement.…”
Section: Anticoagulant Therapymentioning
confidence: 83%
See 2 more Smart Citations
“…A population-based study of cancer patients with acute lower extremity DVT demonstrated an improvement in PE-free survival on long-term follow-up in patients with IVCF insertion (for any indication) compared to those without (HR, 0.69; 95% CI, 0.64-0.75). 106 The proportion of new DVT among patients who received IVCF was slightly lower than in patients who did not receive IVCF (18.7% versus 22.1%; respectively, P < 0.001). A prospective cohort study of cancer patients with acute PE or lower extremity DVT used propensity score matching to compare 30-day outcomes between patients with IVCF placement because of a significant bleeding risk versus patients without IVCF placement.…”
Section: Anticoagulant Therapymentioning
confidence: 83%
“…A prospective cohort study of cancer patients with acute PE or lower extremity DVT used propensity score matching to compare 30-day outcomes between patients with IVCF placement because of a significant bleeding risk versus patients without IVCF placement. 107 PE-related mortality was lower with than without filter insertion (0.8% versus 4.0%; respectively, absolute reduction –3.2% [95% CI, –6.5% to –0.5%]). The recurrent VTE rate was higher in the IVCF group than in patients without IVCF (7.3% versus 3.2%; absolute increase 4.1% [95% CI, 0–8.3%].…”
Section: Anticoagulant Therapymentioning
confidence: 89%
See 1 more Smart Citation
“…In another cohort study, a significant lower risk of PE-related mortality (0.8% vs 4.0%; p = 0.04) were observed in patients receiving IVCF due to contraindication against anticoagulation compared with those who did not, without significant between-group difference regarding the major bleeding rate (6.1% vs 5.7%; p = 0.85). However, recurrent VTE rates were higher in patients who received IVCF compared with those who did not (7.3% vs 3.2%; p = 0.05) [18].…”
Section: Treatment Of Established Cancer-associated Vte Within 6 Monthsmentioning
confidence: 87%
“… 27 Another propensity-matched retrospective study compared the use of inferior vena cava filters in 247 patients with cancer, in whom anticoagulant therapy was contraindicated, with 247 matched patients with cancer but without inferior vena cava filters, reporting a non-significant lower risk of death (12·2% vs 17·0%, p=0·13), and a significantly lower risk of pulmonary embolism-related mortality (0·8% vs 4·0%; p=0·04). 28 …”
Section: Guideline Recommendationsmentioning
confidence: 99%